Coconut basal stem rot is manageable - Snehalatharani, A; Devappa, V; Rajappan, K; Maheswarappa, H P (Indian Horticulture, 2019)
Of the different treatments imposed, basal application of T. viride gives significant results. The mixture of 50g of T. viride talc formulation + 5 kg of neem cake as basal application per palm per year is most effective and none of the palms treated with this method shows symptoms even after 3 years. Overall yield performance of field after treatment imposition is good. Nut yield per acre before treatment imposition is recorded as 700, whereas that after treatment imposition is 1000.